PaCQL: A new type of treebank search for the digital humanities - Anton Karl Ingason (IJCoL)
This article describes PaCQL (Parsed Corpus Query Language), a novel query language for carrying out research on parsed historical corpora, an important task for the digital humanities. PaCQL implements and enhances many of the most important features of earlier software that is designed for computational research in historical syntax and combines such functionality with a search engine which employs a fast in-memory index that cuts down waiting time in many realistic research scenarios. A web interface is provided with an automatically created summary of the main quantitative findings. The primary goal of this project is to contribute to the development of software tools which are designed from the ground up specifically with the needs of the digital humanities in mind.